Skrining Fitokimia dan Potensi Antidiabetes Ekstrak Etanol Herba Ciplukan (Physalis Angulata L) pada Tikus Putih (Rattus Novergicus) yang Diinduksi Aloksan - Maliangkay, Hendra Pratama; Rumondor, Rolef; Kantohe, Mynia (Jurusan Pendidikan Biologi, Fakultas Ilmu Pendidikan, Universitas Timor, 2019)
The purpose of this study to determine the anti-diabetic potential of ciplukan herbal ethanol extract (Physalis angulata L) in white rats (Rattus norvegicus) induced alloxan given intraperitoneally and comparing its effectiveness with glibenclamide. This study uses 5 groups namely giving aquadest as normal control, giving alloxan as a negative control, giving alloxan and glibenclamide as a positive control and the ethanol extract of ciplukan herbal with a dose of 150 mg/kg BB and 300 mg/kg BB. Blood glucose measurement performed on day 0 (three days after induction), day 7, and day 14. The results showed that ethanol extract of ciplukan herbal (Physalis angulata L) can lower blood glucose levekls. A dose of 150 mg/kg BB have percentage decrease in blood glucose levels on day 7 and day 14 respectively by 14.1%and 70.5%. dose of 300 mg/kg BB have a percentage decrease in blood glucose levels on day 7 and day 14 respectively by 70.5%.and 69.5%. a dose of 150 mg/kg BB is more effective as an anti-diabetic compared with a dose of 300 mg/kg BB. Ethanol extract of ciplukan herbal (Physalis angulata L) also has an activity to repair damaged pancreatic-Î² cells in rats (Rattus norvegicus) induced by alloxan.